Perubahan Strategi SDM pada PT Matahari Departemen Store Bekasi Cyber Park - Shinta Nurul Ramadhanty; Djuni Thamrin; Matdio Siahaan; Joseph Martinio Jocrien Renwarin; Hadita Hadita (Sekolah Tinggi Ilmu Administrasi Yappi Makassar Jl. Sumba no 46, Kota Makassar, Sulawesi Selatan, 2024)
The purpose of this study is to find out the change in strategy in PT Matahari Jabatan Tbk Bekasi Cyber Park.This study uses a qualitative research method with data collection techniques carried out by observation, interview and documentation techniques. Research that aims to describe and describe events and phenomena that occur in the field and present data systematically, factually and accurately about facts or phenomena that occur in the field. The research informants in this study are 1 manager, 2 supervisors, and 2 general employees as informants. So there are 5 people who are supporting informants. The results of this study show that the strategy changes. Related to HR strategies Human change is related to the roles, attitudes, perceptions and expectations of employees in the organization. Meanwhile, changes in the structure include authority, work flow, and, labor in the organization. Meanwhile, changes in the structure include authority, work flow, and, labor in the organization. Human resources greatly determine the successful process of an organization's performance. Human resource development is to make it easier to realize the company's goals, because the quality of human resources is considered capable of carrying out their duties and functions as employees in an organization.